Genetic Dissection of Root Adaptive Responses to Water Stress - Melebari, Dalia (2023)
Land plants have evolved root adaptive responses which facilitate water exploration by sensing soil moisture availability, then modifying traits such as the orientation and velocity of primary root growth, as well as the frequency and patterning of root branching. Exploiting such plant root traits conferring resilience to water stress provides a novel way to close the yield gap but requires new knowledge about these adaptive processes and their underlying molecular mechanisms. This PhD thesis addressed the molecular mechanisms underpinning two water stress adaptive root responses, namely hydrotropism (Chapters 3 & 4) and xerobranching (Chapter 5; Mehra et al, 2022, Science). Hydrotropism orients root growth towards the best available soil moisture source. In contrast, the xerobranching response prevents the initiation of lateral roots when roots lose contact with moist soil. Despite their obvious developmental differences, I have demonstrated root adaptive responses are regulated by the same abiotic stress hormone, abscisic acid (ABA; Chapter 3-5; Mehra et al, 2022). This observation raises important questions about whether ABA regulates both root water stress adaptive responses using identical, related or distinct molecular mechanisms and/or components? My thesis studies have focused on revealing how ABA is transported during these root adaptive responses. Following a root hydrotropic stimulus, ABA must move from its phloem source to target cortex (response) cells. To address whether specialised transporters are involved, an amiRNA transportome library was screened to discover novel genes that regulate ABA mobilisation in Arabidopsis roots (Chapter 3). Putative ABA transporters were identified such as ATP binding cassette family (ABCG); a MATE transporter family member DTX1; and a glucosinolate influx transporter GTR1 (Chapter 4). This PhD study also revealed that ABA is a key regulator of the root adaptive response xerobranching (Chapter 5; Mehra et al, 2022). This represents an ABA-dependent root adaptive response to loss of contact with moist soil, that is conserved in eudicot and monocot species, which inhibits lateral root development after a xerobranching stimulus. ABA functions as a phloem-derived stress hormone disrupting intercellular communication between inner and outer cell layers via plasmodesmata. The closure of these intercellular pores prevents lateral root branching by impeding the inward passage of the hormone signal auxin.